MODEL ASESMEN INFORMAL KECERDASAN JAMAK ANAK USIA 4 - 5 TAHUN - Wijaya, Intan Prastihastari; Kuntjojo (Jurnal Pendidikan Usia Dini, 2018)
This research was conducted to create an informal assessment model of multiple intelligences for 4 and 5 years old children. The design used for this research is the research and development design by adapting the Borg and Gall model. The result of an informal assessment model is an informal multiple intelligences assessment models for 4 and 5 years old children, the assessors are classroom teachers, the time and place for conducting the assessment is flexible. The first implementation of the assessment model was done in TK Negeri Pembina Kota Kediri with research subjects of group B of 38 children and the second implementation was done in TK Negeri Pembina Kecamatan Mojoroto Kediri with the subject of research of Group A of 61 children. The results of the experiment showed that the multiple intelligences assessment models of children age 4 and 5 years old meet the validity and reliability requirements and as well as its easy application in Kindergarten education institutions. Keywords: informal assessment model, multiple intelligence, 4 and 5 years old childre Desain yang digunakan untuk penelitian ini adalah desain penelitian dan pengembangan dengan mengadaptasi model Borg dan Gall. Model asesmen yang dihasilkan adalah model asesmen informal kecerdasan jamak anak usia 4 dan 5 tahun, pelaksana asesmen adalah guru kelas, waktu dan tempat pelaksanaan asesmen bersifat fleksibel. Uji coba I model asesmen dilakukan di TK Negeri Pembina Kota Kediri dengan subjek penelitian anak Kelompok B sebanyak 38 anak dan uji coba II dilakukan di TK Negeri Pembina Kecamatan Mojoroto Kota Kediri dengan subjek penelitian anak Kelompok A sebanyak 61 anak. Hasil ujicoba menunjukkan bahwa model asesmen kecerdasan jamak anak usia 4 dan 5 tahun memenuhi syarat validitas dan reliabilitas serta mudah untuk diterapkan di lembaga pendidikan Taman Kanak-kanak. Kata Kunci: model asesmen, kecerdasan jamak, anak usia 4 dan 5 tahun